Concept of financial flow management of enterprise corporate security system - Sergienko, O.; Volosnikova, N.; Reshetniak, Natalia; Mashchenko, Maryna; Baranova, Valeria (ТОВ "Фінтехальянс", 2022)
The concept of financial flows management of enterprise corporate security system is developed and justified in the article. The approaches to the assessment and analysis of the financial flow are analyzed. It is determined that the financial flow of enterprises' corporate security system should be understood as financial resources purposeful movement, which is a dynamic set in time and space within the logistics of processes at enterprises. The paper proves that the time factor is an important criterion for the industrial enterprise resource security management effectiveness because the duration of the time of any task depends on many interdependent cycles and parameters. It is emphasized that the vector of strategic goals in the multi-purpose model of integrated logistics processes at enterprises in a particular time period is complexly determined on the basis of various coefficients which are formed by the internal and external institutional environment analysis. It is confirmed that modeling of financial resources of integrated logistics processes makes it possible not only to form the optimal vector of strategic goals of the multipurpose model of integrated logistics processes but also to identify the interconnection between the composition and volume of incoming and outgoing financial flows of all enterprise integrated processes. Material flow management optimization as a key aspect of logistics activities is considered, which is achieved by attracting and allocating financial resources and realized in the financial flows of integrated logistics processes at enterprises. The urgency of the requirements of coherence of material, financial, informational, and other types of resource flows of integrated logistics processes at enterprises is determined. It is proved the topicality and relevance of algorithms implementation for finding and analyzing performance indicators and decision-making criteria, which form the basis of the decision-making system for effective management of industrial enterprises’ resource potential, including financial, in conditions of factors instability and significant changes in the micro and macroeconomic environment.

У статті розроблено та обґрунтовано концепцію управління фінансовими потоками системи корпоративної безпеки підприємства. Проаналізовано підходи до оцінки та аналізу фінансових потоків. Визначено, що під фінансовим потоком системи корпоративної безпеки на підприємствах слід розуміти цілеспрямований рух фінансових ресурсів, що являє собою динамічну сукупність у часі та просторі в межах логістизації процесів на підприємствах. У роботі доведено, що важливим критерієм ефективності управління ресурсною безпекою промислового підприємства є часовий чинник, тому що тривалість часу виконання будь-якого завдання залежить від множини взаємозалежних циклів та параметрів. Наголошується, що вектор стратегічних цілей у багатоцільовій моделі інтегрованої логістизації процесів на підприємствах у конкретний часовий період визначається комплексно на основі різних коефіцієнтів, сформованих за результатами аналізу внутрішнього та зовнішнього інституційного середовища. Підтверджено, що моделювання фінансових ресурсів інтегрованих логістичних процесів дає змогу не тільки сформувати оптимальний вектор стратегічних цілей багатоцільової моделі інтегрованої логістизації процесів, а й виявити взаємозв’язки між складом та обсягом вхідних і вихідних фінансових потоків усіх інтегрованих процесів на підприємствах. Розглянуто оптимізацію управління матеріальними потоками як ключового аспекту логістичної діяльності, що досягається шляхом залучення та розподілу фінансових ресурсів, що реалізуються у фінансових потоках інтегрованої логістизації процесів на підприємствах. Визначено актуальність вимог узгодженості матеріальних, фінансових, інформаційних та інших видів ресурсних потоків інтегрованої логістизації процесів на підприємствах. Доведено актуальність та релевантність упровадження алгоритмів знаходження й аналізу показників ефективності та критеріїв прийняття рішень, які складають основу моделі системи прийняття рішень ефективного управління ресурсним потенціалом, у тому числі фінансовим, промислового підприємства в умовах нестабільності факторів і суттєвих змін у мікро- та макроекономічному середовищі.
Концепція управління фінансовими потоками системи корпоративної безпеки підприємства
Keywords: financial flow; financial resources; integrated logistics processes; institutional environment; enterprise; corporate security; фінансовий потік; фінансові ресурси; інтегрована логістизація процесів; інституційне середовище; підприємство; корпоративна безпека